Antecedents of Thai Select restaurant brand loyalty in the United Kingdom - Puris Sornsaruht; Sudaporn Sawmong (My University, 2017)
This study examined the determinants of Thai Select restaurant brand loyalty which included restaurant brand image, staff service quality, perceived quality, brand awareness, and brand association on brand loyalty.Of the estimated 1,600 Thai restaurants within the United Kingdom, only 57 have been certified as having the authenticity and quality of Thai Select, which functions as a global branding effort for Thai restaurants by the Thai government.LISREL 9.1 was used to conduct a confirmatory factor analysis, and structural equation modelling to test the 12 hypothesized interrelationships affecting overall brand loyalty.Questionnaires were administered to 550 patrons at 13 London metropolitan restaurants.Results showed that the latent variables staff service quality, brand awareness, restaurant brand image, brand awareness, and perceived quality had a total value of 0.88, 0.54, 0.47, 0.42, and 0.26, respectively.Specifically, dining patrons felt that the most important aspect of staff service quality was that the staff could communicate effectively, were knowledgeable about the food they served, and could deliver the food on time.
Keywords: Brand Loyalty; Kingdom; Customer Service Quality and Loyalty